The Use of Animated Video to Increase Early Childhood Knowledge about Disability and Their Behavorial Intention Towards Disabled Peers - Kurniawati, Farida; Sabila, Hanifah (Indonesian Journal of Disability Studies, 2020)
This study aims to determine the effectiveness of learning through animated video in increasing the knowledge and the behavioral intention of children aged 5-6 years towards children with disabilities. The effectiveness is then analyzed to see whether it can last for a certain period after the learning process.The results of data analysis showed that learning through animated video was quite effective in introducing disability because there was an increase in participants' scores on knowledge and behavioral intention toward people with disabilities. However, the results of data analysis using the Wilcoxon signed-rank test show that there were no significant differences (p> 0.05), both in children's knowledge and behavioral intention toward people with disabilities, both before and after video screening. Two weeks after the intervention period, the results of data analysis also showed an insignificant result. A discussion of the results of the study and some recommendations for further research are written in the end.